The Influence of Firm Value and Disclosure of Sustainability Report on Financial Distress moderated by the Corporate Life Cycle - Yenni Carolina; Sigit Munandar; Aryo Bimo Setya Permana (Jurnal Penelitian Ekonomi Dan Akuntansi, 2024)
This study aims to approve that firm value has effect on financial distress, sustainability report has effect on financial distress and Firm Life Cycle strengthen of firm value on financial distress also firm life cycle strengthen of sustainability report on financial distress. Population in this research is company who listed at LQ45 in 2020 and sample of this research are 32 company with purposive sampling technic. This study using quantitative methode approach. Data analys using logistic regression and moderated regression analysis (MRA) which using SPSS Software. Result of this study are firm value has effect on financial distress, sustainability report has not effect on financial distress and Firm Life Cycle strengthen of firm value on financial distress also firm life cycle doesn’t strengthen of sustainability report on financial distres